Audit Sistem Informasi Keuangan Daerah "SI Rampak Sekar" Menggunakan Framework COBIT 5 (Studi Kasus pada BAPPEDA Provinsi Jawa Barat) - Septian Dwi Priyatmoko; Rendra Trisyanto Surya; Riauli Susilawaty Hutapea (Indonesian Accounting Research Journal, 2021)
Government Regulation Number 56 of 2005 concerning Regional Financial Information Systems is stimulated as the legal basis for the West Java Provincial Government to develop a Regional Financial Information System to assist regional financial management so that it runs effectively and efficiently. During its development, the West Java Provincial Government was able to create an Integrated Planning and Budgeting System between the Provincial Government and the Regional Government of the City of West Java, abbreviated as "SI Rampak Sekar". However, in its implementation, problems are still found, such as non-specific account codes, inaccurate price calculations, SI Rampak Sekar servers that are often down, and the quality of human resources that is difficult to adapt to system developments. Therefore it is necessary to conduct an information system audit to determine the maturity level of SI Rampak Sekar governance. The information system audit in this study was carried out using COBIT 5 framework by selecting key IT Processes in all EDM, APO, BAI, DSS, and MEA domains. The results showed that the maturity of SI Rampak Sekar was at level 2 with the category "Repeatable But Intuitive" meaning that the governance process was still carried out based on routine repetition using certain systematic but not optimal patterns. The results of this maturity level measurement are expected to be input in efforts to improve the quality of SI Rampak Sekar governance.